‘to find out the pathe’: Mapping the Universal Machine in William Cuningham’s Cosmographical Glasse (1559) - Isabelle Fernandes (Journal of Early Modern Studies)
The article places The Cosmographical Glasse (1559), William Cuningham’s magnum opus, in its English and European context. The Cosmographical Glasse appeared during the early modern revolution in mathematics that turned mathematics to practical use by applying it to geography for a better conceptualisation of the globe and universe. Despite the work’s encyclopaedic scope and its author’s pioneering attempt to help readers retrieve the growing body of data that was being amassed by scholars and explorers, the article argues that this first book in English to deal with navigation in relation to astronomy and cosmography stood at a crossroads between the old and new epistemologies as geography both resorted to and confirmed traditional sources of knowledge while challenging them. Limited and flawed as it may be, The Cosmographical Glasse nevertheless added another building block in the construction of a modern sense of cosmography.